2009
DOI: 10.1016/j.jvs.2008.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Sarpogrelate hydrochloride reduced intimal hyperplasia in experimental rabbit vein graft

Abstract: The present results indicate that in vivo blockade of 5-HT(2A) receptors leads to an inhibition of intimal hyperplasia in rabbit vein graft. It is suggested that an increased function of endothelium-derived NO through a reduction in endothelial superoxide production may be a possible underlying mechanism for this. These novel findings support the clinical usefulness of sarpogrelate for preventing intimal hyperplasia in vein graft after bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…The previous studies have shown that the relaxations induced by 5-HT in the arteries including porcine coronary arteries were mediated by activation of 5-HT receptors localized on the endothelial cells [11,12]. In addition, the recent studies indicated that sarpogrelate improved endothelial function in balloon-injured porcine coronary artery [42] and aorta in cholesterolfed rabbits [43] and enhanced ACh-induced, endothelium-dependent NO-mediated relaxation in the vein grafts [44].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have shown that the relaxations induced by 5-HT in the arteries including porcine coronary arteries were mediated by activation of 5-HT receptors localized on the endothelial cells [11,12]. In addition, the recent studies indicated that sarpogrelate improved endothelial function in balloon-injured porcine coronary artery [42] and aorta in cholesterolfed rabbits [43] and enhanced ACh-induced, endothelium-dependent NO-mediated relaxation in the vein grafts [44].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of endothelial cells and vascular smooth muscle cells in response to vascular injury is a major cause of restenosis after stent implantation [2]. Some experimental studies have suggested that sarpogrelate, a selective serotonin (5-hydroxytryptamine (HT)2a ) receptor antagonist and could effectively prevent restenosis and thrombosis after stent implantation because of its antiproliferative and antiplatelet effects [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…11,13, 14 We recently found that the walls of grafted veins displayed a massive increase in the number of SMCs in the intimal layer, and subsequently an accelerated atherogenesis, factors that have been suggested to be responsible for graft occlusion. 15, 16 We also found that the functions of EDNO and endothelium-dependent SMC hyperpolarization activated by endothelium receptor agonists were both impaired in rabbit vein grafts. [17][18][19] However, it is unknown how the surgical operation itself affects the functions of EDNO and EDHF in such grafted arteries and veins.…”
mentioning
confidence: 73%